PHYSICO -CHEMICAL ANALYSIS OF SOIL ADJACENT TO A DUMPING SITE OF MUNCIPAL WASTE - SANTOSH KUMAR SHARMA (International Journal of Multidisciplinary Research and Studies, 2020)
As a result of increasing urbanization and rising population levels, the amount of solid trash that is generated in metropolitan areas around the world has experienced a dramatic uptick. Sometimes hazardous wastes from household and industrial chemicals that should be disposed of in hazardous waste dumps get up in municipal landfills instead. These landfills are designed specifically for the disposal of hazardous trash. After these wastes are disposed of in a landfill, the chemicals in them have the potential to seep into the earth and groundwater through precipitation and surface runoff. The organic material, inorganic salts, and heavy metals found in leachate are present in high concentrations. Disposal of municipal solid waste (MSW) in an unscientific manner has the potential to have a negative effect on all aspects of the ecosystem as well as human health. It is of the utmost importance to conduct leachate, groundwater, and soil monitoring in order to ascertain the level of contamination and to devise appropriate remediation strategies. Monitoring of several physicochemical and biological characteristics was used to determine whether or not there was a deterioration in the quality of the groundwater found in close proximity to MSW disposal sites.